A kind of flexible conductive silver paste for steering wheel and preparation method thereof
By using a combination of micro-sheet silver powder with specific particle size and density and other components, flexible conductive silver paste is prepared, which solves the problems of poor reliability and adhesion of domestic products, and achieves high conductivity and good use durability.
Patent Information
- Application Number
- CN202310879092.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-07-18
AI Technical Summary
At this stage, flexible conductive silver paste for steering wheel has not yet formed mature and stable products in China, and there are problems of poor reliability and poor adhesion, resulting in dependence on imported products.
Microsheet silver powder with an average particle size of 1 to 3 μm and a tap density greater than 3 g/mL is used as the conductive phase, and the components such as ethyl cellulose, terpineol, castor oil, lecithin and butylcarbitol are combined. Flexible conductive silver paste is prepared by high-speed dispersion, three-roll grinding, vacuum filtration and homogeneous stirring.
It realizes high conductivity, good adhesion and durability of conductive silver paste, solves the problems of poor reliability and adhesion of domestic products, and has high performance characteristics suitable for steering wheels.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a conductive silver paste, in particular to a flexible conductive silver paste for a steering wheel and a preparation method thereof. Background Art
[0002] Fatigue driving is an important cause of traffic accidents, so fatigue driving monitoring is a key research area. At present, there are adaptive research directions for detecting fatigue driving both at home and abroad. Most of them use physiological equipment to monitor the driver's EEG, ECG and other physiological signals, or design vehicle-mounted equipment to detect vehicle information during fatigue driving. At present, using steering wheel grip force signals to test fatigue driving has become a mainstream monitoring method. The grip force-based method has the following advantages: easy signal acquisition, high signal-to-noise ratio, low cost, and will not affect normal driving operations during the monitoring process. However, the accuracy of this method is relatively low, and it is necessary to configure internal electrodes with higher signal accuracy to make the steering wheel grip force signal test system become mainstream.
[0003] The internal electrode with high signal accuracy is very complicated to make. Among them, low-temperature co-fired ceramic technology is the preferred way for modularization and integration of future electronic devices due to its excellent thermal, electrical, mechanical and process characteristics. LTCC technology is an emerging technology for integrated packaging. The so-called LTCC technology is to prepare low-temperature sintered ceramic powder into a raw porcelain tape with very precise thickness and density, and use laser drilling, microporous grouting, precision conductor silver paste printing and other processes to form a set circuit pattern on the raw porcelain tape, and then bury multiple passive components in it, and stack many layers of raw porcelain sheets with printed conductive patterns together, and then sinter at below 900°C to form a passive integrated component with a three-dimensional circuit network. At the same time, ICs and active devices can also be mounted on its surface to make a three-dimensional circuit containing passive components to make a passive / active integrated functional module.
[0004] Ceramic antennas, a miniaturized antenna, can be built into the steering wheel to become a high-precision, low-cost module. Block ceramic antennas use the LTCC manufacturing process, which can effectively reduce the size of the antenna and conceal the design graphics inside the antenna. Since the dielectric constant of ceramic antennas is higher than that of PCB circuit boards, the use of ceramic materials as the dielectric material of the antenna can effectively reduce the size of the antenna. Therefore, raw ceramic materials are more suitable for Bluetooth modules with low power consumption. The LTCC process involves many processes, mainly including slurry configuration, casting, cutting, punching, filling holes, printing, lamination, isostatic pressing, cutting, debinding, sintering, end-capping, silver burning, electroplating, braiding, etc. According to the requirements of the product process characteristics, the process will be adjusted.
[0005] The accuracy of the LTCC electrodes used in the steering wheel is directly related to the performance of the matching flexible conductive silver paste. Flexible conductive silver paste is a paste ink made by dispersing conductive materials (gold, silver, copper and carbon) in a binder, commonly known as paste ink. It has a certain degree of conductivity and can be used for printing conductive points or conductive lines. Metallic conductive inks, carbon conductive inks, etc. have reached practical use and are used for printed circuits, electrodes, electroplating bases, keyboard contacts, printed resistors and other materials. Flexible conductive silver paste consists of conductive fillers, adhesives, solvents and additives. Conductive fillers use the best conductive silver powder and copper powder, and sometimes gold powder, graphite, carbon black (special conductive carbon black is now available), carbon fiber, nickel powder, etc. Synthetic resins used as adhesives include epoxy resins, alkyd resins, phenolic resins, vinyl chloride-vinyl acetate copolymer resins, etc. The solvent used is an environmentally friendly medium-boiling screen ink special solvent with a boiling point in the range of 120-230°C. In addition, additives such as dispersants, lubricants, coupling agents, etc. are added as needed. The properties required for flexible conductive silver paste include: conductivity (antistatic), adhesion, printability, hardness and solvent resistance, etc. Thick film color paste is used for IC integrated circuits, capacitors, electrodes, etc., and resin-based ink is used for printed circuits, membrane switches, antistatic packaging, etc.
[0006] At present, the flexible conductive silver paste for steering wheels still relies on imported products, and there are no mature and stable products in China. Domestic products have the defects of poor reliability and poor adhesion, so the research and development of this product is of great significance. Summary of the invention
[0007] The purpose of the present invention is to provide a flexible conductive silver paste for a steering wheel and a preparation method thereof.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] A flexible conductive silver paste, comprising the following components and contents by weight:
[0010]
[0011] Furthermore, the bending-resistant silver powder is a micro-flaky silver powder with an average particle size of 1 to 3 μm and a tap density greater than 3 g / mL.
[0012] Furthermore, the average particle size of the glass powder is less than 5 μm.
[0013] Furthermore, the glass powder includes the following components and their weight percentages: SiO2 30%, Al2O3 10%, B2O3 8%, CaO 6%, ZnO 10%, MgO 10%, and BaO 26%.
[0014] A method for preparing a flexible conductive silver paste comprises the following steps:
[0015] S1: Ingredients: Add flexural-resistant silver powder, glass powder, ethyl cellulose, pinene alcohol, castor oil, lecithin, and butyl carbitol and mix evenly to obtain a raw material mixture;
[0016] S2: high-speed dispersion to obtain a dispersed raw material mixture;
[0017] S3: Three-roll grinding: Grind the dispersed raw material mixture by a three-roll grinder, and repeat steps S2 to S3 after grinding until the fineness is less than or equal to 10 μm;
[0018] S4: vacuum filtration;
[0019] S5: Stir evenly to obtain a flexible conductive silver paste.
[0020] Furthermore, in step S2, the high-speed dispersion is: stirring the raw material mixture for 20 to 25 minutes.
[0021] Further, in step S3, three cumulative cycles of three-roll grinding are performed, and during the first three-roll grinding, the roller gap is controlled at 0.3-0.35 mm, the second roller gap is controlled at 0.2-0.25 mm, and the third roller gap is controlled at 0.15-0.2 mm.
[0022] Furthermore, in step S4, the mesh size of the sieve used for vacuum filtration is 300-400 meshes.
[0023] Furthermore, in step S5, during the homogenous stirring process, the vacuum degree is 0.1-0.15 MPa, and the stirring time is 3-5 min.
[0024] Compared with the prior art, the present invention has the following characteristics:
[0025] 1) The present invention uses a micro-flaky silver powder with an average particle size of 1 to 3 μm and a tap density of >3 g / mL as the conductive phase. The micro-flaky silver powder has a high tap density, which can make the sintered film denser and have good conductivity. At the same time, the flaky silver powder has a certain degree of bending resistance, so that the conductive silver paste has good durability after forming;
[0026] 2) The present invention uses ethyl cellulose as a film-forming agent, pinene alcohol, castor oil, and lecithin as solvents, and castor oil as a leveling agent and softener. In order to ensure the smoothness and compactness of the silver film after sintering, the organic carrier should not be too violent in the reaction and decomposition. As a universal solvent, pinene alcohol has good solubility; as a solvent, lecithin can emulsify and disperse solid particles; castor oil is a good leveling agent and softener, which makes the slurry have good fluidity and storage stability; butyl carbitol can increase the recovery of the slurry, reduce the carrier hardness, modulus, softening temperature and brittle temperature, and improve the elongation, bendability and flexibility. DETAILED DESCRIPTION
[0027] The present invention is described in detail below with reference to specific embodiments.
[0028] A flexible conductive silver paste, comprising the following components and contents by weight:
[0029]
[0030] Among them, the average particle size of the bending-resistant silver powder is 1 to 3 μm, and the tap density is greater than 3g / mL. The micro-flake silver powder with an average particle size of 1 to 3 μm and a tap density of >3g / mL is used as the conductive phase. The selection basis is as follows: the electrode printed in the LTCC antenna is printed on the substrate using a 325-mesh stainless steel screen. The line width is extremely fine, 50 to 80 μm, and the line spacing is 50 to 80 μm. The wiring requirements are very fine. If the accuracy of the pattern after silver paste printing is not enough, the sintering mold will produce burrs, skew or deformation, affecting the function of the wiring, thereby hindering the function of the entire component. In addition, it is also necessary to consider that the LTCC process is sintered at 850 to 900 ° C. If nano silver powder is used, the melting point of glass powder and silver powder is too different, and the adhesion after sintering is poor. A higher tap density can make the sintered film denser and the electrode wire has good conductivity. Therefore, the tap density of the silver powder used should be greater than 3g / mL. The silver powder used must be in the form of flakes, so that it can have a certain degree of bending resistance.
[0031] The average particle size of the glass powder is less than 5 μm.
[0032] The glass powder includes the following components and their weight percentages: SiO2 30%, Al2O3 10%, B2O3 8%, CaO6%, ZnO 10%, MgO 10%, BaO 26%. B2O3 can improve the chemical stability of glass, reduce the softening point, and increase the melting speed; Al2O3 can reduce the linear expansion coefficient of glass and improve the mechanical strength of glass; CaO and BaO can accelerate the melting and clarification process and improve the stability of glass; ZnO can improve acid resistance and water resistance.
[0033] Ethyl cellulose is selected as the film-forming agent, pinene alcohol, castor oil, and lecithin are selected as solvents, and castor oil is selected as a leveling agent and softener. In order to ensure the smoothness and density of the silver film after sintering, the flammability and decomposition of the organic carrier should not be too severe. As a universal solvent, pinene alcohol has good solubility; as a solvent, lecithin can emulsify and disperse solid particles; castor oil is a good leveling agent and softener, which makes the slurry have good fluidity and storage stability; butyl carbitol can increase the recovery of the slurry, reduce the carrier hardness, modulus, softening temperature and brittle temperature, and improve the elongation, bendability and flexibility.
[0034] A method for preparing a flexible conductive silver paste comprises the following steps:
[0035] S1: Ingredients:
[0036] Mettler BBA211 electronic scale was used as a weighing tool, and with the recording component, the operator could add raw materials with corresponding codes according to the panel display value, with the accuracy controlled within one ten-thousandth. The order of weighing ingredients is: adding bending-resistant silver powder, glass powder, ethyl cellulose, pinene alcohol, castor oil, lecithin, and butyl carbitol and mixing evenly to obtain a raw material mixture; when the amount of reagent added is small, the JY20002 electronic scale is used.
[0037] S2: High speed dispersion:
[0038] After weighing, move the material barrel to the high-speed mixer platform, then turn on the high-speed mixer switch, lower the stirring head to 2 cm from the bottom of the barrel, turn on the frequency conversion switch to 70 Hz, set the timing and stir continuously for 20 to 25 minutes, and finally observe that the ink is a silver-gray slurry without silver powder particles, which means it is evenly dispersed to obtain a dispersed raw material mixture;
[0039] S3: Three-roll grinding: Grind the dispersed raw material mixture by a three-roll grinder, and repeat steps S2 to S3 after grinding until the fineness is less than or equal to 10 μm;
[0040] Preferably, the three-roll grinding step requires three cycles of grinding on a three-roll grinder, and each time the ink is rolled, the high-speed dispersion step needs to be performed again. Then, the gap between the fast roller and the middle roller of the three-roll grinder is continuously and gradually controlled. The roller gap of the first grinding of low-temperature conductive ink is controlled at 0.3mm-0.35mm, the roller gap of the second grinding is controlled at 0.2-0.25mm, and the roller gap of the third grinding is controlled at 0.15-0.2mm. In the process of adjusting the roller gap, the uniformity of the discharge should also be observed. After three grindings, the process detection is carried out. The next step can be carried out only when the detected fineness is less than or equal to 10μm.
[0041] S4: Vacuum filtration, used to filter out large particles of impurities produced during the grinding process.
[0042] Preferably, the device includes a stainless steel cavity connected to a high-power vacuum pump, a stainless steel material barrel is placed in the stainless steel cavity, and finally a 350-mesh stainless steel net is installed above the stainless steel cavity as needed. When in use, first turn on the vacuum pump switch, then continuously pour the dispersed silver chloride conductive silver paste on the stainless steel net, and use a rubber scraper to continuously flatten the silver paste so that it can be quickly filtered into the built-in stainless steel material barrel. At this time, the flexible conductive silver paste in the material barrel is a semi-finished product to be inspected;
[0043] Usually, a vacuum filtration device or a suction filtration device with the same filtration capacity can also be used, and the mesh number of the sieve used is preferably 350 mesh;
[0044] S5: Homogenizing and stirring:
[0045] The use of homogenizer equipment mainly removes bubbles and prevents silver powder from settling. The conductive ink after homogenization will be very fine and uniform. When using, set the vacuum degree to 0.10-0.15Mpa, and then put the canned ink into the homogenizer and stir for 3-5 minutes. After homogenization and stirring, a flexible conductive silver paste can be directly shipped out for filling.
[0046] The following embodiments are implemented based on the above technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.
[0047] Example:
[0048] A flexible conductive silver paste for a steering wheel, the raw material components and ingredients are shown in Table 1, the unit is g.
[0049] Table 1
[0050] Material Name Example 1 Example 2 Example 3 Example 4 Example 5 Bending resistant silver powder 80 80.1 80.2 80.3 80.4 Glass powder 3 3 3 3 3 Ethyl cellulose 6.5 6.4 6.3 6.2 6.1 Terpineol 5 5 5 5 5 castor oil 3 3 3 3 3 Lecithin 2 2 2 2 2 Butyl Carbitol 0.5 0.5 0.5 0.5 0.5
[0051] The method for preparing the above-mentioned flexible conductive silver paste for a steering wheel comprises the following steps:
[0052] S1: Silver powder pretreatment:
[0053] The silver powder was placed in an ethanol solution of adipic acid and stirred at room temperature for 2.5 hours, taken out and dried at 85°C for 14 hours, and passed through a 300-mesh sieve to obtain pretreated silver powder;
[0054] S2: Ingredients:
[0055] Mettler BBA211 electronic scale is used as a weighing tool, and with the recording component, the operator can add raw materials with corresponding codes according to the panel display value, and the accuracy is controlled within one ten-thousandth. The order of weighing ingredients is: add bending-resistant silver powder, glass powder, ethyl cellulose, pinene alcohol, castor oil, lecithin, and butyl carbitol and mix them evenly to obtain a raw material mixture; since the amount of additives added is small, a JY20002 electronic scale can be used.
[0056] S2: High speed dispersion:
[0057] After weighing, move the material barrel to the high-speed mixer platform, then turn on the high-speed mixer switch, lower the stirring head to 2 cm from the bottom of the barrel, turn on the frequency conversion switch to 70 Hz, set the timing and stir continuously for 25 minutes, and finally observe that the ink is a silver-gray slurry without silver powder particles, which means it is evenly dispersed to obtain a dispersed raw material mixture;
[0058] S3: The three-roll grinding step requires three cycles of grinding on the three-roll grinder. After each rolling of the ink, the high-speed dispersion step needs to be performed again. Then the gap between the fast roller and the middle roller of the three-roll grinder is controlled step by step. The roller gap of the first grinding of low-temperature conductive ink is controlled at 0.35mm, the second roller gap is controlled at 0.25mm, and the third roller gap is controlled at 0.15mm. In the process of adjusting the roller gap, the uniformity of the discharge should also be observed. After three grindings, the process detection is carried out. The next step can be carried out only when the detected fineness is less than or equal to 10μm.
[0059] S4: Vacuum filtration: Use a 350-mesh stainless steel mesh to filter out large particles of impurities produced during the grinding process;
[0060] S5: Homogenizing and canning:
[0061] The use of a homogenizer is mainly to degas the conductive ink and prevent the silver powder from settling. The conductive ink after homogenization will be very fine and uniform. When using it, set the vacuum degree to 0.10Mpa, and then put the canned ink into the homogenizer and stir for 3 minutes. After homogenization and stirring, a flexible conductive silver paste can be directly shipped out of the warehouse for filling to obtain a flexible conductive silver paste. The performance test is shown in Table 2.
[0062] Table 2
[0063]
[0064]
[0065] Among them, the solid content test method is: put the silver glue into a weighing bottle to weigh and obtain weight 1, put it into a 690℃ sintering furnace for 5 minutes, weigh it again to obtain weight 2, calculate weight 2 / weight 1, and take three samples to find the average.
[0066] Viscosity test method: Pour the slurry into a Brookfield V-Ⅱ viscometer, place it in a constant temperature water bath at 25°C for 5 minutes, and read the viscosity value.
[0067] Fineness test method: Pour the slurry into the scraper fineness meter to test the fineness and read the fineness value.
[0068] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A flexible conductive silver paste, characterized in that: It includes the following components and contents by weight: 80~83 parts of bending resistance silver powder; 3~5 parts of glass powder; Ethyl cellulose 5-10 parts; 5-10 parts of terpineol; 3-4 parts castor oil; 2-3 parts of lecithin; Butyl carbitol 0.5~1 part; The bending-resistant silver powder is a micro-flaky silver powder with an average particle size of 1-3 μm and a tap density greater than 3 g / mL, and the bending-resistant silver powder is also pretreated before mixing, and the pretreatment includes: placing the silver powder in an ethanol solution of adipic acid at room temperature and stirring for 2.5 hours, taking it out and drying it at 85° C. for 14 hours, and passing it through a 300-mesh sieve to obtain the pretreated silver powder.
2. The flexible conductive silver paste according to claim 1, characterized in that: The average particle size of the bending-resistant silver powder is 1-3 μm.
3. The flexible conductive silver paste according to claim 2, characterized in that: The bending-resistant silver powder is a micro-flaky silver powder with a tap density greater than 3 g / mL.
4. The flexible conductive silver paste according to claim 1, characterized in that: The average particle size of the glass powder is less than 5 μm.
5. The flexible conductive silver paste according to claim 1, characterized in that: The glass powder includes the following components and their weight percentages: SiO2 30%, Al2O3 10%, B2O3 8%, CaO 6%, ZnO 10%, MgO 10%, and BaO 26%.
6. The method for preparing a flexible conductive silver paste according to claim 1, characterized in that: The method comprises the following steps: S1: Ingredients: Add flexural-resistant silver powder, glass powder, ethyl cellulose, pinene alcohol, castor oil, lecithin, and butyl carbitol and mix evenly to obtain a raw material mixture; S2: high-speed dispersion to obtain a dispersed raw material mixture; S3: Three-roll grinding: Grind the dispersed raw material mixture by a three-roll grinder, and repeat steps S2 to S3 after grinding until the fineness is less than or equal to 10 μm; S4: vacuum filtration; S5: Stir evenly to obtain a flexible conductive silver paste.
7. The method for preparing a flexible conductive silver paste according to claim 6, characterized in that: In step S2, the high-speed dispersion is: stirring the raw material mixture for 20 to 25 minutes.
8. The method for preparing a flexible conductive silver paste according to claim 6, characterized in that: In step S3, three cumulative cycles of three-roll grinding are performed, and during the first three-roll grinding, the roller gap is controlled at 0.3-0.35 mm, the second roller gap is controlled at 0.2-0.25 mm, and the third roller gap is controlled at 0.15-0.2 mm.
9. The method for preparing a flexible conductive silver paste according to claim 6, characterized in that: In step S4, the mesh size of the sieve used for vacuum filtration is 300-400 meshes.
10. The method for preparing a flexible conductive silver paste according to claim 6, characterized in that: In step S5, during the homogenous stirring process, the vacuum degree is 0.1-0.15 MPa, and the stirring time is 3-5 min.
Citation Information
Patent Citations
Process for preparing conductive slurry for crystalline silicon solar cell front electrode
CN102097183A
Silver paste for positive electrode of crystalline silicon solar cell and preparation method thereof
CN102157219A
Stretch-proof waterborne conductive printing ink, and preparation method thereof
CN110054937A
Preparation method of nano-silver paste for electric field driven jet micro-nano 3D printing
CN111180107A
High-conductivity conductive silver paste and preparation method thereof
CN112820440A